Demographic, Clinical and Management Characteristics of Newly Diagnosed COPD Patients in Turkey: A Real-Life Study - Suerdem M (International Journal of COPD, 2020)
Mecit Suerdem,1 Hakan Gunen,2 Levent Akyildiz,3 Aykut Cilli,4 Tevfik Ozlu,5 Esra Uzaslan,6 Oznur Abadoglu,7 Hasan Bayram,8 Arif Hikmet Cimrin,9 Bilun Gemicioglu,10 Zeynep Misirligil11 1Department of Chest Diseases, Faculty of Medicine, Selcuk University, Konya, Turkey; 2Sureyyapasa Chest Diseases and Thoracic Surgery Training and Research Hospital, Health Sciences University, Istanbul, Turkey; 3Department of Pulmonary Medicine, Memorial Dicle Hospital, Diyarbakır, Turkey; 4Department of Chest Diseases, Faculty of Medicine, Akdeniz University, Antalya, Turkey; 5Department of Chest Diseases, Faculty of Medicine, Karadeniz Technical University, Trabzon, Turkey; 6Department of Chest Diseases, Faculty of Medicine, Uludag University, Bursa, Turkey; 7Private Office of Pulmonary and Allergic Diseases, Istanbul, Turkey; 8Koc University Research Center for Translational Medicine (KUTTAM), Department of Pulmonary Medicine, Koc University School of Medicine, Istanbul, Turkey; 9Department of Chest Diseases, Faculty of Medicine, Dokuz Eylul University, Izmir, Turkey; 10Department of Pulmonary Diseases, Faculty of Cerrahpasa Medicine, Istanbul University, Cerrahpasa, Turkey; 11Department of Pulmonary and Allergic Diseases, Ankara Liv Hospital, Ankara, TurkeyCorrespondence: Mecit SuerdemDepartment of Chest Diseases, Faculty of Medicine, Selcuk University, Konya, TurkeyTel +90 332 241 21 81-82Fax +90 332 241 21 84Email mecsuerdem@gmail.comPurpose: In order to determine the clinical and sociodemographic characteristics of newly diagnosed treatment-naïve asthma and COPD patients in Turkey, a multicenter study in 2012 was initiated . We aimed to investigate the characteristics and therapies of COPD patients in the original study in more detail.Patients and Methods: This nation-wide, multicentric, non-interventional, prospective, real-life observational cohort study was conducted in 122 centers. The newly diagnosed patients were not receiving any treatment before the recruitment. Their general characteristics, the combined GOLD 2011 COPD categories and exacerbation histories were noted. The patients were followed up with 3 voluntary visits for 1 year. Their adherence to the inhaled treatment according to GOLD 2011 was evaluated during follow-up visits.Results: The study included 776 COPD patients. Their mean age was 59.4± 9.1 years, and 11.9% of the patients were female. 35.1% of the patients were in the GOLD 2011 C and D category. 12.6% are frequent exacerbators, and 52.8% had at least one comorbid condition. 71.8% overtreatment rate was detected. Their attendance rates for three follow-up visits became 55.9%, 32.9% and 18.7%, respectively. The adherence rate to the treatment was measured as 81.9%.Conclusion: Although these patients were diagnosed for the first time, the GOLD C and D categories and frequent exacerbator phenotype were found at a high rate. They were usually prescribed an overtreatment regimen. We think that newly diagnosed COPD patients should be evaluated carefully, and best effort should be made to treat these patients in accordance with the recommendations of the major COPD guidelines.Keywords: COPD, newly diagnosed, treatment naïve, exacerbations